Promoting Inclusivity Through Technology: A Literature Review in Educational Settings - Wulandari, Citra Eka; Firdaus, Fauzan Akmal; Saifulloh, Farida (LPPM Universitas Terbuka, 2024)
Inclusive education has been a major focus of global education policy conversations over the past few decades. Along with the rapid development of technology, the role of technology in supporting inclusive education has become an increasingly widely explored subject of research. Technology integration in the context of inclusive education involves the use of various tools and platforms that are accessible to students with special needs. The purpose of this research is to explore various aspects of the use of technology in promoting inclusion in education, by identifying opportunities, challenges and important factors that should be considered in order to create a more inclusive and equitable education for all individuals. The research method used is a literature review, exploring data sources such as journal articles, books, research reports and other academic publications relevant to this topic. The results of this study show that technology integration has had a significant positive impact in improving educational accessibility for students, allowing more efficient personalization of learning, and increasing student engagement and participation in the learning process. However, challenges such as technology infrastructure, teacher training, technology suitability, data privacy and necessary policy support need to be addressed for the benefits of technology to be optimized in supporting educational inclusion as a whole.